Snap-buckling and post-buckling analyses of fixed supported beams having initially small circular imperfection under the effect of uniformly distributed vertical load - Atacan, Ayfer Tekin; Yukseler, Receb Faruk (GAZI UNIV, FAC ENGINEERING ARCHITECTURE, 2022)
In this study, snap-buckling and post-buckling behaviors of fixed beams having initially small circular imperfection subjected to uniformly distributed vertical loads are examined. The effect of a parameter related to the geometry of the initially imperfect beam on the buckling values as well as the deformed shapes of the initially imperfect beam, support reactions and internal forces are investigated. The finite difference method and the displacement-controlled Newton-Raphson method are used for the numerical solution of the nonlinear governing differential equations obtained within the framework of the Euler-Bernoulli beam theory. It is observed that the concerning geometric parameter significantly effects the buckling values, deformed shapes of the initially imperfect beam, support reactions and internal forces.
Keywords: Snap-buckling; initially imperfect beam; nonlinear equations; finite difference method; displacement-controlled Newton-Raphson method; INPLANE ELASTIC STABILITY; SHALLOW ARCHES; NONLINEAR-ANALYSIS; SHELLS; Engineering